THE RELATIONSHIP OF SELF-CONFIDENCE TO INDEPENDENCE IN LEARNING INDONESIAN CLASS 3 AT SDN MANGUN JAYA 03 - Ningsih, Niviana; Dariyanto, Dariyanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2024)
If students experience low self-confidence, if it cannot be handled properly, it will result in low learning independence and can hinder students' progress in the learning system. Therefore, the problem that will be studied in this research is: